Dissociable effects of APOE-ε4 and β-amyloid pathology on visual working memory - Lu, Kirsty (Nat Aging, 2021)
Although APOE-ε4 carriers are at significantly higher risk of developing Alzheimer’s disease than non-carriers(1), controversial evidence suggests that APOE-ε4 might confer some advantages, explaining the survival of this gene (antagonistic pleiotropy)(2,3). In a population-based cohort born in one week in 1946 (assessed aged 69-71), we assessed differential effects of APOE-ε4 and β-amyloid pathology (quantified using (18)F-Florbetapir-PET) on visual working memory (object-location binding). In 398 cognitively normal participants, APOE-ε4 and β-amyloid had opposing effects on object identification, predicting better and poorer recall respectively. ε4-carriers also recalled locations more precisely, with a greater advantage at higher β-amyloid burden. These results provide evidence of superior visual working memory in ε4-carriers, showing that some benefits of this genotype are demonstrable in older age, even in the preclinical stages of Alzheimer’s disease.